Sugarcane residue incubated in soil at different temperatures and nitrogen fertilization - de Almeida, Risely Ferraz [UNESP]; Silveira, Camila Haddad; da Mota, Raquel Pinheiro; Arruda, Everton Martins; Naves, Emmanuel Rezende; de Souza, Luma Castro [UNESP]; Mendonça, Eduardo de Sá; Wendling, Beno (My University, 2015)
The sugarcane residue deposited on the soil is an alternative source of nutrients, which can serve as a soil conditioner in soil conservation. The effects of sugarcane harvest systems, especially with the residue incorporated into, or left on the soil surface, and the resulting impact on the availability of plant nutrients are little known. The aim of this work was to study the influence of nitrogen fertilization (0 and 120 kg ha-1 of N) and the management of sugarcane residue (surface and incorporated) on the availability of nutrients in soils incubated at three temperatures (20, 25 and 30° C). It was concluded that there is an increase of 6.89 % N in the soil with the sugarcane residue incorporation, compared to the surface management. Total soil N increases were obtained with sugarcane residue, especially when incorporated and associated with nitrogen fertilization. There was no effect of the treatments on soil microbial biomass carbon content (S-MBC), labile carbon (Labile-C), calcium (Ca+2), magnesium (Mg+2) and phosphorus (P). Potassium is the nutrient that presents rapid mineralization from the residue into the soil. With the addition of the incorporated and soil surface residue there occurred increases in the final K+ mineralization of 42.05 % and 11.98 %, respectively.
Keywords: C/N ratio; Carbon; Immobilization; Latosol; Nutrients; Straw